Okinawan Consciousness and Identity Salience and Development among Okinawan University Students Studying in Hawai‘i - Taira, Kazufumi; Yamauchi, Lois A (Journal of International Students, 2018)
After Japan’s annexation in 1879, Okinawa came under the unprecedented influence of Japanization. This research examined how learning in Hawaiʻi influenced the Okinawan sense of identity of 11 Okinawan students. Grounded theory analysis of interview transcripts indicated that students became more conscious as Okinawan through encounters and interactions with local people, including Okinawans, and Hawaiians in Hawai‘i, and Okinawan events and activities there. Participating in an Okinawan club at the university provided opportunities for the students to express their Okinawan identity, interact with club members, and take responsibility as representatives of Okinawa, which promoted students’ Okinawan consciousness and identity salience.